Foreign Medical Teams in support of the Ebola outbreak: a UK military model of pre-deployment training and assurance. Issue 3 (26th May 2016) - Gibson, Christopher; Fletcher, T; Clay, K; Griffiths, A
Abstract : We discuss the training methodology developed and utilised to prepare UK military medical teams to establish an Ebola Treatment Centre in Sierra Leone. We highlight the process of identifying and mitigating nosocomial risk in the Pre-Deployment Training process, encompassing the challenges of developing, training and assuring a capability at pace, which deployed to deliver high quality clinical care to patients with Ebola Virus Disease.